The United Nations Human Rights Council at 16: a creature of compromise or a compromised creature?. Issue 1 (2nd January 2023) - Sweeney, Caroline
ABSTRACT: As the United Nations (UN) Human Rights Council approaches its sixteenth birthday, this article examines its performance to date. It highlights the Council's achievements, including in upscaling its preventative capabilities, addressing thematic issues of cultural sensitivity and historically divisive country situations, and establishing a truly universal mechanism for reviewing the human rights record of every UN member state. However, it also identifies major weaknesses, including the persistent appointment of states with poor human rights records to the Council, escalating reprisals against individuals who cooperate with the Council's mechanisms, inefficient working methods, impotence in the face of chronic human rights emergencies, and unequal opportunities for civil society engagement. The article reveals that the most significant progress has been achieved, not through formal inter-governmental negotiations, but incrementally as a result of effective outreach and international assistance, all propelled forward by civil society activism. It concludes that at this pivotal moment in the Council's lifetime, strong leadership and thoughtful diplomacy are needed now more than ever to achieve concrete improvements in the human rights situation on the ground or, at the very least, to avoid retrogression.